Pengaruh Budaya Organisasi, Kompensasi, Dan lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasaan Kerja Sebagai Variabel Intervening (Kantor Bappeda Kabupaten Bima NTB) - Hasanuddin, Hasanuddin; Surati, Surati; Ramly, Amir Tengku (Jurnal Manajemen, 2020)
This study aims to determine and analyze the influence of work culture, compensation, and work environment on employee performance with job satisfaction as an intervening variable. The idea of improving employee performance is in line with the need to improve the quality of sustainable development plans in planning agencies. Using a case study of employees at the Bima District Development Planning Agency (BAPPEDA Kabupaten Bima), this research highlights the importance of improving employee performance for achieving the quality of planning and budgeting policies. The criteria used in the purposive sampling are based on the status of position IIIa and a minimum working period of 3 years. The head of the BAPPEDA office was not selected as a respondent in the study. The total number of study participants was 51 employees. Data analysis using SPSS statistical program and parallel path analysis method. The results showed two interrelated patterns, first work culture and work environment have a positive and significant effect on job satisfaction, while compensation has a positive and insignificant effect on job satisfaction. Second, work culture and work environment have a positive and significant effect on employee performance, while compensation has a negative and significant effect on employee performance, and job satisfaction has a positive and insignificant effect on employee performance. This study suggests the importance of improving work culture and work environment, as well as providing compensation in fulfilling job satisfaction and employee satisfaction in order to have salary fairness, recognition of work dedication and individual needs to improve work performance